Optimizing Value-Added Tax (VAT) Collection Through Tax Service Quality, Tax Audits, And Tax Compliance - Noverina, Erika Damayanti; Hartinah , Siti (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2025)
VAT is an objective consumption tax that is applied to transactions involving goods and services regardless of the financial capacity of the consumers. One important element in improving the state's financial capacity to support financing for sustainable development is optimizing VAT revenue. By analyzing the effects of tax service quality, tax audits, and tax compliance on VAT income, this study aims to explore taxpayer behavior while filing VAT returns. Multiple linear regression analysis is one of the quantitative methods used in this investigation. With a sample size of 60 data points, the secondary data under investigation were obtained from the Jakarta Kramat Jati Tax Office as monthly time series data for the years 2020–2024. SPSS version 22 was used to process the data. The results of the study indicate that value-added tax (VAT) revenues are not significantly impacted by the quality of tax services. On the other hand, value-added tax (VAT) income greatly benefits from tax audits and compliance. Additionally, VAT income is impacted by audits, compliance, and the quality of tax services.